A case report of synchronous primary gastric hodgkin lymphoma and lung adenocarcinoma and literature review - Kuan, Jew Win; Noraidah, Masir (Wolters Kluwer - Medknow, 2023)
We report a rare case of a 58-year-old woman who was initially diagnosed as primary gastric (PG) T-cell non-Hodgkin lymphoma, which later was revised as PG Hodgkin lymphoma (HL) with dissemination to the lung (stage IV). The lung lesion was later found to be lung adenocarcinoma (LA) and the diagnosis was revised again as synchronous primary gastric Hodgkin lymphoma (PGHL) and LA which, to our knowledge, was not reported before. This case illustrated the need of vigilance in the diagnosis of lymphoma at uncommon sites and the clinical challenges in managing synchronous malignancies. The rationale of clinical suspicion, the association between PGHL and Epstein–Barr virus, Helicobacter pylori, and other infections, and synchronous PGHL and LA were discussed.